Politicized scientists: Credibility cost of political expression on Twitter - Eleonora Alabrese; Francesco Capozza; Prashant Garg (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2025)
As social media becomes prominent within academia, we examine its reputational costs for academics. Analyzing Twitter posts from 98,000 scientists (2016-22), we uncover substantial political expression. Online experiments with 4,000 U.S. respondents and 135 journalists, rating synthetic academic profiles with different political affiliations, reveal that politically neutral scientists are seen as the most credible. Strikingly, political expressions result in monotonic penalties: Stronger posts more greatly reduce the perceived credibility of scientists and their research and audience engagement, particularly among oppositely aligned respondents. Two surveys with scientists highlight their awareness of penalties, their perceived benefits, and a consensus on limiting political expression outside their expertise.
Keywords: C93; D72; D83; I23; Z10; 330; Twitter; Scientists' Credibility; Polarization; Online Experiment